Home Team and Visiting Team in Applied Environmental Aesthetics - Sepänmaa, Yrjö (Filozofski vestnik, 2007)
The core question in aesthetics now and in the future is, how to combine philosophical theory with practice. Though reference is made to applied philosophy, and particularly to applied ethics, it is seldom made to applied aesthetics, even though we have a social need for it. The function of applied environmental aesthetics is to lay a foundation for practical actions. The goal is to connect the theoretical side closely to everyday problem solving. This means proceeding from a "passive" outsider aesthetics to an "active", influencing and participating insider aesthetics. The process begins with a theory of applicability, after which actual problem cases follow. The aesthetic point of view is united with ethical, social, and cultural discussions, as well as with the expertise of environmental professionals in education, administration, design and planning, business, etc. The theoreticians and the practitioners form two teams, which should meet and co-operate with each other. In stepping from being a bystander to becoming a participant, the aestheticians will link their work to a network of specialists and professionals.